In-vitro and in-vivo studies of 4D printed shape memory scaffolds with bioactive fillers and coating for enhanced bone tissue regeneration. (1st October 2022) - Zhou, Wanmei; Dong, Xueming; He, Yang; Zheng, Wei; Leng, Jinsong
Abstract: Bone tissue engineering is considered one of the pivotal treatments for bone defects in patients. However, the conventional strategies for repairing irregular and complex bone defects are highly unsatisfactory, and appropriate repairing of bone defects remains a challenge. In recent years, smart scaffolds integrated with multiple functions have emerged as promising alternatives for the treatment of various bone defects. In this study, 4D printed shape memory polymer (SMP) scaffolds containing bioactive fillers (hydroxyapatite and alendronate) and collagen–dexamethasone (Col–Dex) coating were fabricated, and their microstructures, porosity, mechanical properties, and biological functions were thoroughly investigated. The SMP scaffolds manufactured in this study could be programmed into temporary shapes of small sizes and then recovered to working sizes and shapes under an alternating magnetic field to fill bone defects. In addition, the biological studies including cytotoxicity tests, osteogenesis-related gene expressions, fluorescence staining imaging, and animal experiments demonstrated the effective biological activities and osteogenic effects of the 4D printed SMP scaffolds, with potential applications in bone tissue regeneration. In other words, the prepared 4D printed scaffolds with bioactive fillers and the Col–Dex coating will provide an efficient approach for personalized bone tissue repair as well as enhanced bone tissue regeneration.